Slavoj Zizek’s Criticism of Neoliberalism and Radical Political Subjects - Nanto, Yohanes De Brito; Madung, Otto Gusti (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2024)
Neoliberalism strongly endorses private property rights, free markets, and free trade. In the neoliberal economic system, the role of the state is to create and protect the existence of the market. This article aims to discuss Zizek’s critique of neoliberalism and his account of the radical subject. In this article we try to show that neoliberalism has negative impacts on developing countries, among which are the ecological crisis, economic crisis, and the privatization of national assets. We further elaborate on Zizek’s conviction that the presence of radical subjects can solve this problem by breaking through neoliberalism as The Big Other. The post-liberal ideology that he sees as an alternative for creating people’s welfare is “new communism,” which is different from the old communism proposed by Lenin. This communism emphasizes global solidarity in dealing with global problems and reinvigorates the role of the state as a facilitator to support the national economy.